Conceptual clarification of the playful engagement in social interaction of preschool-aged children with autism spectrum disorder (ASD). Issue 3 (23rd February 2019) - Godin, Julie; Freeman, Andrew; Rigby, Patty
ABSTRACT: Children with autism spectrum disorder (ASD) demonstrate limited playfulness. Their difficulty engaging in meaningful interaction with others renders playful engagement in social interactions a challenge. Although little direct evidence exists regarding the promotion of these children's playful engagement, links can be established with many traits cited in play and social interaction studies. This paper presents the results of a conceptual clarification exercise regarding the key behaviours associated with the construct of playful engagement in preschool-aged children with ASD. Behaviours were identified based on hallmark deficits in early social interactions and play of children with ASD. The analysis revealed the following behaviours: positive affect, engagement, imitation, joint attention, initiation of social interaction, social responsiveness, flexibility, child's laughter in funny situations and giving and reading non-verbal cues. In conclusion, a conceptually coherent stage has been set for exploring the literature regarding interventions to promote the playful engagement of preschool-aged children with ASD.